Anticancer activity of polyphyllin I in nasopharyngeal carcinoma by modulation of lncRNA ROR and P53 signalling. (9th August 2019) - Hong, Feilong; Gu, Wenyue; Jiang, Jin; Liu, Xinge; Jiang, Hao
Abstract: Nasopharyngeal carcinoma (NPC) is the most common aggressive squamous cell carcinoma in head and neck cancers. Although advanced radiochemotherapy has been applied, the prognosis of NPC patients still remains poor due to the regional relapse and distant metastasis. Polyphyllin I (PP I) is extracted from natural herb Paris polyphylla that has been widely used in cancer treatment and long non-coding RNA (lncRNA) has been reported to play a key role in the anti-tumour activity of PP I. In this study, it has been found that PP I inhibited the proliferation and induced apoptosis of NPC cells in a dose-dependent manner. A higher level of lncRNA regulator of reprogramming (ROR) expression was detected in NPC cell lines compared with normal nasopharyngeal cell line and PP I must significantly down-regulate the expression level of lncRNA ROR. LncRNA ROR/P53 signalling was essential for PP I-suppressed NPC progression. These data indicated that PP I suppressed tumour growth and induced apoptosis of NPC in vitro and in vivo through down-regulation of lncRNA-ROR, subsequently upregulating of P53 signalling. LncRNA ROR may be a potential therapeutic target and PP I would be a promising candidate for NPC treatment.